Organizational evolution: socio-biological basis for understanding the metaphor (2015)
The purpose of this paper is to provide an approach to the metaphorical use of Darwin’s evolutionist view in a variety of areas of knowledge –social sciences, anthropology, sociology, psychology and economics. A theoretical analysis of the links between these areas and business organizations is carried out resulting in a succinct theoretical foundation about the interrelationships of evolution, as a biological concept, with the business reality. The latter, like any species, must adapt to the environment in the struggle for existence, and must, in addition, co-evolve in order to increase its chances of survival. Finally, unaddressed aspects or contradictions are pointed out which suggest possible outlooks for future research studies.